Relationship between the shoot characteristics and plant resistance to vascular-streak dieback on cocoa - Agung Wahyu Soesilo; Indah Anita Sari (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2014)
Vascular-streak dieback (Oncobasidium theobromae) is a serious disease on cocoa damaging the vegetative tissue especially on the branches and leaves. This research was aimed to identify the relationship between characteristics of sprouting ability and VSD resistance to confirm the response of cocoa to pruning treatment on VSD control and developing criteria for selection. Trial was carried out at Kaliwining Experimental Station of ICCRI, a VSD-endemic area by using 668 plants of hybrid populayion which were derivated from intercrossing among seven clones performing different response to VSD. The resistance was evaluated by scoring the plant damage with the scale of 0-6 on drought season in the year of 2009 and 2011. The characteristics of sprouting ability was assessed by recording the pruned trees for the variables of the number of re-growth shoot, shoot height, number of new shoot per pruned branches, shoot diameter and number of leaves per shoot. It was analyzed that the variables of the number of shoot per pruned branches, shoot diameter, shoot height and number of leaves per shoot were not significantly correlated to the score of VSD damage. Grouping of the resistance also performed similar results whereas mean of the sprouting variables were not different among group but the percentage of sprouted branches tend to be higher with the higher of the resistance (lower score). This result confirmed any mechanism of tolerance on VSD resistance by accelerating shoot rejuvenation on resistant plant. Key words : vascular-streak diaback, cocoa, resistance, characteristics of sprouting